2012
DOI: 10.4049/jimmunol.1202322
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of Regulatory T Cells during Viral-Induced Inflammatory Lesions

Abstract: Ocular HSV-1 infection can result in SK, a blinding immunoinflammatory lesion that represents an immunopathological response to the infection. CD4+ T cells are the main orchestrators, and lesions are more severe if the regulatory T cell response is compromised from the onset of infection. Little is known about the role for Foxp3+ CD4+ Tregs during ongoing inflammatory reactions, which is the topic of this report. We used DEREG mice and depleted Treg at different times after infection. We show that lesions beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 40 publications
2
55
0
Order By: Relevance
“…Depletion of NK cells has been shown to enhance mCMV titers and mCMV-specific T cell responses during acute mCMV infection (22)(23)(24)(25)(26), which might be the reason for the strong effect reported by Arens et al (20). Unlike with mCMV, the expansion of Tregs has been found in mice infected with other herpesviruses, like herpes simplex virus (HSV) (12,27). It is currently not known why mCMV induces such weak Treg responses, which is clearly different from what occurs in many other viral infections.…”
Section: Fig 3 Mcmv-specific Cd8mentioning
confidence: 86%
“…Depletion of NK cells has been shown to enhance mCMV titers and mCMV-specific T cell responses during acute mCMV infection (22)(23)(24)(25)(26), which might be the reason for the strong effect reported by Arens et al (20). Unlike with mCMV, the expansion of Tregs has been found in mice infected with other herpesviruses, like herpes simplex virus (HSV) (12,27). It is currently not known why mCMV induces such weak Treg responses, which is clearly different from what occurs in many other viral infections.…”
Section: Fig 3 Mcmv-specific Cd8mentioning
confidence: 86%
“…MDSCs or MDSC-LCs accumulated in HSV-1-infected corneas (34,130,154), but it remains unclear whether these cells demonstrated inhibitory activity. In one study, F4/80 -GR1 + cells accrued in the corneas of HSV-1-infected mice and the authors concluded, based on nuclear morphology, that these infiltrating cells were not MDSCs, however, functional studies were not provided (130).…”
Section: T Cellsmentioning
confidence: 99%
“…Treg cells play a critical role of regulating effector T cells, NK cells, neutrophils, monocytes, and macrophages early during viral infections, mitigating the pathology incurred by the immune response and prolonging survival of the infected mice (57)(58)(59)(60). The presence of virus-specific memory Treg cells can preserve lung function by limiting CD8 T cell response and reduc- ing pathology during homologous influenza rechallenge (61).…”
Section: Figmentioning
confidence: 99%